ANALISIS KOMPOSISI VEGETASI DAN ASOSIASI ANTAR JENIS DOMINAN PADA KAWASAN HUTAN KONSESI IUPHHK HT PT. DWIMA INTIGA - Karmila Karmila; Muhammad Muchtar Effendy; Syam’ani Syam’ani (Jurnal Sylva Scienteae, 2020)
Forests save a lot of natural resources which are called megadiversity area and it is very diverse, one of the forest is PT IUPHHK forest concession area. Most of the Intiga trees grow various types of plants,  from seedlings, saplings, poles, and trees. Therefore, it is important to do research on the composition of vegetation and the dominant inter-species association so that later it can be used as a consideration for the management of production forests. The results showed that not all of the vegetation that can be  found at each growth level due to live competition between one to another. It is found 74 species of vegetation in a community, 44 species of seedlings, 46 species of stems, 38 species of piles and 26 species of trees. lime, stakes and poles are dominated by mahang while trees are dominated by latex species. The type that is positively associated with a significant level off 1% (3.84) is the type of tarap and madang with a coefficient of 0.290.Keywords: Vegetation;association between dominant species